Intimacy in marital relationship: effect of internet usage - Nik Norazira Abdul Aziz,; Nor Azlili Hassan,; Norazilah Buhari, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The internet and its usage into the everyday lives of a significantly large population has tremendously changed the way people communicate and interact. Since the advent of the internet, couples, families, and individuals of all ages are being impacted by the internet in many ways. This article takes a closer look at how the internet can affect the marital intimacy on married men and women. The purpose of this study is to examine any possible impact internet use may have on an intimate marital relationship. The present study sought to examine the time spent on the internet, as it relates to intimacy and relationships satisfaction experienced in marital relationships. This study analyzed data from a survey of 300 Malaysian married men and women in Selangor, Malaysia. Data was presented on the level of their awareness and knowledge concerning to the relationship between their marital intimacy and internet usage. The findings indicated that married men and women understand that controlling of internet usage is vital because this may affect the relationship in a marriage. This study showed that the majority married men and women remain faithful and trust each other. The results also found that they still can regulate their internet usage and time spent online. Hence, this shows that they give priority to their marriage. The result from this study may offer valuable information about the level of internet usage among married couples in Malaysia that also can be used as a baseline to guide treatment programme and assessment.